Creation and the world of science : the re-shaping of belief - Peacocke, A. R. (Arthur Robert) (Oxford ; New York : Oxford University Press, 2004)
A.R. Peacocke's "Creation and the World of Science", an expanded version of his 1978 Bampton Lectures, was widely recognized as a key work on the relation of the sciences to religion, in general, and Christian theology in particular. It has long been seen as a formative contribution to the wide-ranging investigations, which now, internationally, constitute this intensely active field. This new reprinting contains the original and influential text and also contains a new supplement containing key references to the literature of recent years as well as indicating the author's current position on central themes. It constitutes an essential reference and starting point for the contemporary discussion of key issues in the dialogue between the sciences and theology
The two books -- Cosmos, man, and creation -- Chance and the life-game -- Nature's hierarchies : "things visible and invisible" -- The "selfish gene" and "what men live by" -- Evolved man and God Incarnate -- Man in creation -- Creation and hope.
Originally published: Oxford : Clarendon Press; New York : Oxford University Press, 1979.
Includes bibliographical references and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Creation; Religion and science; Religion and Science; Création.; Religion et sciences; creating (artistic activity); creation (doctrinal concept); RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; Creation; Religion and science; Schepping; Geloof en wetenschap; Electronic book